Study on post-partum uterine involution by Ultrasonography and progesterone profile in local goats in Iraq: Souhayla O Hussain1, Khawla A Hussain2 and Ahmed A. Al-Ani 3 - Hussain, Souhayla O. (The Iraqi Journal of Veterinary Medicine, 2016)
The study was conducted to investigate and characteriz the time of uterine involution in local goats in Iraq by measuring the uterine diameter, uterine lumen (mm) and monitoring early post-partum ovarian activity as proved by Ultrasonography and progesterone assessment in local goats. 15 goats were submitted to examine from day 3 to 40 after kidding by Ultrasonography. Trans abdominal ultrasound approach was performed from day 3 to 5 after kidding and continued by trans rectal approach to follow up the uterine involution until day 40. Progesterone levels were measured starting from day of parturition, then a weekly measure until day 34 of post-partum period. Progesterone was assayed by Radio immune assay. The obtained results showed that complete of uterine involution started at day 26 (6.67) % and completed at day 34 post-partum in all does (100%). on the other hand involution of the uterus was completed at day 26, 27, 28, 29, 31, 33 after parturition with a percentage of 6.67%, 13.34%, 33.34%, 40%, 46.67%, 66.67%, 73.34% and 80% respectively. Average uterine lumen (mm) from days 3-7, 8- 14, 15- 21, 22- 28, 29 -35 and 36-40 were 9.02, 5.82, 5.14, 3.51, 2.66, and 2.0 (mm) respectively. Average uterine diameter (mm) was 40.25, 33.9, 31.4, 25.57, 20 .15 and 16.35 at day 3-7, 8- 14, 15-28, 29-35 and 36-40 respectively. Regarding progesterone profile, results indicated that the mean value of the hormone was 0.267±0.005 ng /ml at parturition and the values were 0.320±0.007, 0.414±00.5, 0.536 ±0.013, and 1.945 ±0.129 ng/ ml at day 7, 14, 21 and day 30, respectively. It could be concluded that Ultrasonography image proved to be a valuable and safe tool in monitoring uterine involution and measuring of progesterone is a precise biological marker for the detection of resumption of ovarian cyclist during post-partum period.